Administration of Immunoglobulins in SARS-CoV-2-Positive Patient Is Associated With Fast Clinical and Radiological Healing: Case Report - Carannante, Novella; Fiorentino, Giuseppe; Corcione, Antonio; Di Sarno, Raffaele; Spatarella, Micaela; Maturo, Nicola; Fragranza, Fiorentino; Di Micco, Pierpaolo (Frontiers in Medicine, 2020)
Polyclonal preparation of IgM as adjuvant therapy has been reported as relevant immunomodulant therapy in several infectious diseases. The SARS COV2 outbreak has been characterized by different therapeutic approach around the world but without univocal clinical responses. Immunomodulant treatment with hydroxychlorochine and biologics as tocilizumab have not univocal and satisfactory results in COIVD19 populatio. So, we treated our selected patient with interstitial multifocal pneumonia, positive to COVID19 with polyclonal preparation of IgM as adjuvant therapy obtaining in few days a clinical remission and serum conversion with IgG antiCOVID19 and associated improvements in radiological findings. So based on our experience we suggest to extend this kind of immune adjuvant therapy to large based population.